2015
DOI: 10.1177/1359104515577487
|View full text |Cite
|
Sign up to set email alerts
|

Horses for courses? A qualitative exploration of goals formulated in mental health settings by young people, parents, and clinicians

Abstract: The results suggest that goals may capture areas not captured by other normed outcome measures. In particular, goals may capture higher order, underlying factors, such as confidence, resilience, coping, and parenting factors that may not be explored by other measures. The differences across perspectives also link to existing literature suggesting a different focus on treatment based on perspectives and highlights the potential importance when jointly agreeing goals of ensuring the voice of the child/young pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 44 publications
5
46
0
Order By: Relevance
“…Most straightforwardly, they highlight the known link between mental health problems and impaired quality of life, underlining the relevance of measuring quality of life as a key outcome of mental health interventions [9][10][11]. This is especially significant given the acknowledgment that, alongside decreasing symptoms, a key goal of intervention may be to ensure that mental health difficulties have minimal impact on functioning and quality of life [11,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most straightforwardly, they highlight the known link between mental health problems and impaired quality of life, underlining the relevance of measuring quality of life as a key outcome of mental health interventions [9][10][11]. This is especially significant given the acknowledgment that, alongside decreasing symptoms, a key goal of intervention may be to ensure that mental health difficulties have minimal impact on functioning and quality of life [11,27].…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that by addressing these questions we can contribute to the wider debate about how quality of life should be considered, measured and supported in relation to interventions in mental health generally and in child mental health specifically [9][10][11].…”
mentioning
confidence: 99%
“…coping and resilience [44]. It would also be useful to further explore whether goals were routinely used alongside or instead of other measures.…”
Section: Discussionmentioning
confidence: 99%
“…In the present article, goals are specific outcomes a child, young person, or family wants to achieve in accessing mental health services [48]. Commonly set goals by children accessing services include coping with specific difficulties, personal growth, and independence, and commonly set goals by parents accessing services include managing specific difficulties their child has, parent-specific goals such as increased knowledge of their child’s difficulties, and improving self or life [44]. It has been suggested that goal formulation and tracking may be especially useful for service users with particular needs, where progress may not be expected in terms of symptom reduction [6], which may include children with learning disabilities or developmental difficulties.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Interactions during this period might well serve to set the scene for working relationships and determine the strength of joint planning that follows. In general mental health literature, idiographic-goal tools are typically valued by professionals and families for such reasons (Edbrooke-Childs et al 2015;Jacob et al 2016) and frequently used in general mental health services for children and adolescents (Law 2011;Wolpert et al 2012). Relative to other procedures, methods for agreeing goals specific for PBS have however received little research attention (Dunlap and Fox 2007) and in practice may be an overlooked opportunity to get things right.…”
mentioning
confidence: 99%